Institutional Constraints and Enablers: An Introduction to the Special Topic Forum on Extreme Operating Environments. (September 2016) - Gerde, Virginia W.; Michaelson, Christopher
This article is the guest editors' introduction to the Special Topic Forum on Extreme Operating Environments appearing in Business & Society . The forum includes two articles accepted after review and revision. The two articles address the macro-level aspects of business's role in society in terms of accessing resources and markets and in terms of being a change agent or enabler to promote a better or more stable local economy. The articles also provide case studies of businesses developing, getting access to resources and markets, and affecting the larger institutional environment despite great uncertainty and harsh operating environments where the traditional assumptions of stability and security are not available. This Special Topic Forum is published in cooperation with Business & Professional Ethics Journal which, working with the guest editors, has published two other articles that address the more micro-level aspects and the ethical dilemmas business may face in extreme operating environments.